Approaches to reporting grade uncertainty in high nugget gold veins - Dominy, Simon; Edgar, W. (2012)
High nugget effect gold veins are generally considered to be one of the most challenging of deposit types to evaluate and exploit. To potential investors and mining companies, they are viewed as high risk because of the associated uncertainties in the grade estimate and general paucity of reserves at production start-up. Despite the well-known risks, these deposits are often high grade and have a grade upside which makes them potentially attractive. The reporting of resource grade is of importance and perhaps even more so is the reporting of the associated uncertainty attached to the grade estimate. The quoting of the estimated grade within a grade range is recommended to achieve more complete and useful disclosure. The definition of the grade range can be somewhat subjective, ranging from opinion-based through to data-based estimates and geostatistical conditional simulation. Whichever approach is used, the over-riding issue must be the provision of enough data of appropriate quality and full disclosure to the public of relevant uncertainties. © 2012 Institute of Materials, Minerals and Mining and The AusIMM.